Effects of Hygroscopic Potash Lye Catalyst Concentration on the Waste Chicken Fat Methyl Ester Production - Razak, N.H.; Hashim, H.; Yunus, A.N.; Ghafar, F.; Zulkafli, N.I. (Journal of Engineering and Technology (JET), 2016)
The work presented in this study demonstrates the effect of the hygroscopic potash lye catalyst concentration on the waste chicken fat methyl ester production. The aim of this paper is to determine the effect of temperature, catalyst ratio and methanol ratio on fatty acid methyl ester (FAME) yield from waste chicken fat (WCF). The finding shows the optimum yield were 95.4 % with 0.006 w/w hygroscopic potash lye catalyst and 0.3 w/w methanol at 50°C. The final analysis of this study identifies the FAME density was 873.4 kg/m3, the iodine value, 117 g I/100 g and the acid value, 0.561 mg KOH/g. Moreover, the compositions of fatty acids were 0.22 % of methyl laurate (C13H26O2), 19.98 % of methyl palmitate, (C17H34O2), 41.08 % of methyl stearate (C19H38O2) and 0.17 % of methyl linoleate (C19H34O2) henceforth this FAME produced exhibit properties very similar to ASTM D6751 and EN 14214. This study confirms that the FAME transesterified from waste animal fats with the hygroscopic potash lye catalyst could be a potential alternative to petrodiesel.